Long-term health benefits of stroke prevention with apixaban versus vitamin K antagonist warfarin in patients with non-valvular atrial fibrillation in Germany: a population-based modelling study. (4th March 2019) - Himmler, Sebastian; Müller, Malina; Ostwald, Dennis; Seddik, Ahmed; Basic, Edin; Hradetzky, Eva
ABSTRACT: Background : Patients with non-valvular atrial fibrillation (NVAF) have a five times higher stroke risk. For more than 50 years, vitamin K antagonists (VKAs) have been the primary medication for stroke prevention. Apixaban, a non-vitamin K oral anticoagulant (NOAC), has demonstrated better efficacy and safety characteristics than the VKA warfarin in the ARISTOTLE trial. This study aims to quantify the potential societal effects of using apixaban instead of VKA in the German NVAF population from 2017 to 2030. Methods : Using an existing Markov model and a dynamic population approach, we modelled the health benefits of apixaban in patients with NVAF compared to VKA therapy in the German population from 2017 to 2030. Results : The results represent the extrapolated direct long-term health benefits of apixaban over VKA therapy for the German NVAF population. From 2017 until 2030, the use of apixaban instead of a VKA could avoid 52, 185 major clinical events. This includes 15, 383 non-fatal strokes or SEs, 22, 483 non-fatal major bleeds, and 14, 319 all-cause deaths, which correspond to 109, 887 life years gained. Conclusion : This study demonstrated that using apixaban instead of VKA for stroke prevention can lead to considerable reduction in cardiovascular events.